Cortical reorganization in elite athletes: Lessons in plasticity for brain injury treatment - Hoad, D.; Desikan, L.; Flanagan, P.; Shribman, S.; Hammond, P.; Greenwood, R.; Rothwell, J. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Introduction. Muscles that habitually perform a bilateral activation receive a stronger bilateral corticospinal innervation. Athletes perfecting control of a movement that involves muscles acting bilaterally may alter the cortical representation of that muscle. With training a single cortical origin may provide a stronger bilateral control. Transcranial Magnetic Stimulation (TMS) provides a non-invasive means of mapping the cortical representation and characterizing corticospinal control of a muscle. Using TMS we demonstrate a pattern of cortical reorganization whereby ipsilateral projections from one hemisphere are strengthened in elite athletes, having implications both for training athletes and treating brain injury patients. Methods. Canoe-polo players who had accumulated over 10,000 hours of training and represented their country in world-cup competition were compared to healthy controls. EMG was recorded from abdominal External Obliques, ipsilateral and contralateral to the side of cortical stimulation. Background activation at 10% of Maximum Voluntary Contraction was produced. Neuronavigation guided the TMS coil to points on a scalp grid 1cm apart, centred on the site of optimal stimulation (Hotspot) for the contralateral muscle. Each point in the surrounding cortex was then stimulated at 120% of the active motor threshold (aMT). Analysis. EMG was rectified and Motor Evoked Potentials (MEP) were averaged for each grid point. MEPs were normalized to mean+1S.D. of background activity. Normalised responses for each grid coordinate expressed as mean %Background Activity were pooled for the two groups. The pooled maps were analysed by comparing with an unpaired t-test the mean response at sites 0cm, 1cm, 2cm and 3cm from the centre of the grid (i.e the contralateral hotspot) for ipsilateral and contralateral muscles. Results. Bilateral MEP`s were seen in all 20 subjects. Of note there was no significant difference between athletes and controls for contralateral muscle representation. This is important as it establishes that peripheral factors such as muscle size do not explain observed differences. In ipsilateral muscle the mean response at 1 cm from the hotspot was 246%+/-21(mean +/-SEM) for athletes and 107+/-11 for controls (p=<0.001), at 2 cm 266 +/-17 for athletes and 108 +/-7 for controls (p=<0.001) and at 3cm 219 +/-14 for athletes and 75+/-15 for controls (p=<0.001). Discussion. We show that athletes have a cortical region surrounding the contralateral muscle representation that is able to produce ipsilateral responses. Athletes drive plasticity to increase the motor cortex map of ipsilateral muscles when bilateral axial muscle activation is important. This knowledge provides the athlete with a basis for alternative training strategies, and provides the neurologist with a therapeutic target in the intact hemisphere after brain injury.